Antimicrobial-Resistant Escherichia coli Strains and Their Plasmids in People, Poultry, and Chicken Meat in Laos - Moser, Aline I.; Kuenzli, Esther; Campos-Madueno, Edgar I.; Büdel, Thomas; Rattanavong, Sayaphet; Vongsouvath, Manivanh; Hatz, Christoph; Endimiani, Andrea (Frontiers in Microbiology, 2021)
Antimicrobial-resistant (AMR) Enterobacterales are widely distributed among the healthy population of the Indochinese peninsula, including Laos. However, the local reservoir of these pathogens are currently not known and possible sources such as agricultural settings and food have rarely been analyzed. In this work, we investigated the extended-spectrum cephalosporin- (ESC-) and colistin-resistant Escherichia coli strains (CST-R-Ec) isolated from the gut of local people, feces of poultry, and from chicken meat (60 samples each group) in Laos. WGS analysis based on both short- and long-read sequencing approaches were implemented. The following prevalence of ESC-R-Ec and CST-R-Ec were recorded, respectively: local people (70% and 15%), poultry (20% and 23.3%) and chicken meat (21.7% and 13.3%). Core-genome analysis, coupled by ST/cgST definitions, indicated that no common AMR-Ec clones were spreading among the different settings. ESC-R-Ec mostly possessed blaCTX-M-15 and blaCTX-M-55 associated to ISEcp1 or IS26. The majority of CST-R-Ec carried mcr-1 on IncX4, IncI2, IncP1, and IncHI1 plasmids similar or identical to those described worldwide; strains with chromosomal mcr-1 or possessing plasmid-mediated mcr-3 were also found. These results indicate a high prevalence of AMR-Ec in the local population, poultry, and chicken meat. While we did not observe the same clones among the three settings, most of the blaCTX-Ms and mcr-1/-3 were associated with mobile-genetic elements, indicating that horizontal gene transfer may play an important role in the dissemination of AMR-Ec in Laos. More studies should be planned to better understand the extent and dynamics of this phenomenon.